The Influence of Interpersonal Communication on Employee Performance at Pt. Unilever Indonesia Tbk Ciracas Region Sales Division - S, Jeiin Maren; Sahab, Nur Dina; Irawan, Pristanto Ria (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Interpersonal communication applied in the company environment is communication that is more dialogical in nature with an emphasis on self-disclosure which can often lead to feedback and understanding of one another, this is done within the PT. Unilever Indonesia Tbk Ciracas Region Sales Division, as an effort to improve employee performance. The purpose of this research is to determine interpersonal communication on employee performance at PT Unilever Indonesia Tbk Sales Division for the Ciracas Region. This research uses a quantitative descriptive method with data collection techniques through distributing questionnaires and library data. In this research, the saturated sampling method used was 30 employees of PT. Unilever Indonesia Tbk Ciracas Region Sales Division, using simple linear regression data analysis techniques. The results of this research show that not available the influence of interpersonal communication on the performance of PT Unilever Indonesia Tbk Sales Division Ciracas Region employees. low influence has an influence contribution of 7,8% on employee performance variables. It is hoped that the results of this research will contribute to further research.